Incidencia del liderazgo situacional en el Índice de satisfacción laboral de los empleados de la ESPAM - Vega Chica, Mayra Liuviana (2017)
In the following article the leadership style of ESPAM was analyzed to know his incidence in the index of labor satisfaction of 234 employees of the institution. The results of this investigation as well as the conclusions and recommendations are exposed in the final paragraphs of the document. The above mentioned results demonstrate that in the ESPAM there is a leadership style of Direction in equipment considered as the ideal one since he promotes a balance sheet between the orientation to the persons and the orientation to the results, adapting to the different situations and individuals as the situational leadership needs it, which gives as consequence a good environment of work and a high index of labor satisfaction.